2016
DOI: 10.1182/blood-2016-03-635219
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of circulating tumor DNA in non-Hodgkin lymphoma

Abstract: Response assessment in lymphoma relies on imaging scans that do not capture biologic processes at the molecular level. Monitoring circulating tumor DNA (ctDNA) with next-generation sequencing–based assays can detect recurrent disease prior to scans and “liquid biopsies” for somatic mutations address tumor heterogeneity, clonal evolution, and mechanisms of resistance to guide precision treatment. Preanalytic collection and processing procedures should be validated and standardized. We describe emerging applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
(54 reference statements)
1
45
0
1
Order By: Relevance
“…Presence of identical clonal T cells in peripheral blood and skin of patients with CTCL, including early stages of mycosis fungoides, has been reported two decades ago and suggested a systemic nature of CTCLs (37)(38)(39). However, recent studies demonstrated that cell-free DNA could be released from solid tumors to circulation and could be detected by deep sequencing of serum/plasma DNA (40)(41)(42). In this study, we detected lymphoma-characteristic TCRg rearrangements in blood for 66% of patients with mycosis fungoides (8/12), albeit at low frequency (Table 1), most often in PBMCs but not in serum or plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of identical clonal T cells in peripheral blood and skin of patients with CTCL, including early stages of mycosis fungoides, has been reported two decades ago and suggested a systemic nature of CTCLs (37)(38)(39). However, recent studies demonstrated that cell-free DNA could be released from solid tumors to circulation and could be detected by deep sequencing of serum/plasma DNA (40)(41)(42). In this study, we detected lymphoma-characteristic TCRg rearrangements in blood for 66% of patients with mycosis fungoides (8/12), albeit at low frequency (Table 1), most often in PBMCs but not in serum or plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Material consisted of mycosis fungoides tumor and plaque skin biopsies (n ¼ 46) collected from 37 patients (median age of patients 66 years, range in the clinic at the Department of Dermatology, Bispebjerg University Hospital (Copenhagen, Denmark) or the Division of Dermatology, University of Alberta (Edmonton, Canada; Supplementary Tables S1 and S2). Peripheral blood was collected from 16 patients with mycosis fungoides and from 5 voluntary healthy control donors (HD; median age 36 years, range [30][31][32][33][34][35][36][37][38][39][40][41][42]. Serum and plasma were separated according to a laboratory protocol, and then DNA was extracted using the EZNA circulating DNA Kit (Omega Biotek, catalog no.…”
Section: Samplesmentioning
confidence: 99%
“…High‐throughput DNA sequencing of ctDNA encoding tumor‐specific mutations also is becoming available as a “liquid biopsy” that can serve as a surrogate for the entire tumor genome and overcome the barrier of spatial and temporal tumor heterogeneity . Using these novel methods, disease‐specific mutations can be detected at diagnosis and followed throughout the course of disease to quantitatively monitor tumor dynamics during treatment and detect emergent mutations that may represent clonal evolution and/or herald resistance to targeted therapy …”
Section: Circulating Tumor Dna In Nhlmentioning
confidence: 99%
“…Precision monitoring of ctDNA after therapy could be a foundational component of precision medicine strategies for NHL. Individual mutations or panels of mutations may be able to predict responsiveness to targeted therapies designed to overcome known mechanisms of treatment resistance . A recent paper of ibrutinib in DLBCL demonstrated that the presence of both MYD88 and CD79B mutations was highly predictive of responsiveness .…”
Section: Clinical Applications Of Circulating Tumor Dnamentioning
confidence: 99%
“…[6][7][8] As a surrogate for the composite tumor genome, ctDNA as a liquid biopsy integrates all the genetic lesions from a tumor and can provide more comprehensive information than a single-tissue biopsy. 9 It is notable that ctDNA was identified as an early molecular biomarker for response to panobinostat. The clearance of ctDNA after a few cycles of combination chemotherapy is predictive for response in DLBCL, but the observation of similar patterns with targeted therapy paves the way to test new agents using ctDNA as a surrogate translational end point.…”
mentioning
confidence: 99%